Nitric oxide-induced rapid decrease of abscisic acid concentration is required in breaking seed dormancy in Arabidopsis - Liu, Yinggao (The New phytologist, 2009)
Nitric oxide (NO) has been reported to be involved in breaking seed dormancy but its mechanism of action is unclear. Here, we report that a rapid accumulation of NO induced an equally rapid decrease of abscisic acid (ABA) that is required for this action in Arabidopsis. Results of quantitative real-time polymerase chain reaction (QRT-PCR) and Western blotting indicate that the NO-induced ABA decrease correlates with the regulation of CYP707A2 transcription and (+)-abscisic acid 8'-hydroxylase (encoded by CYP707A2) protein expression. By analysing cyp707a1, cyp707a2 and cyp707a3 mutants, we found that CYP707A2 plays a major role in ABA catabolism during the first stage of imbibition. Fluorescent images demonstrate that NO is released rapidly in the early hours at the endosperm layer during imbibition. Evidently, such response precedes the enhancement of ABA catabolism which is required for subsequent seed germination